Knowledge of Secondary School Students on HIV/AIDS in Kirkuk Province / Iraq. - Tahir, Suhella S.; Kadir, Mohammed A.; Akbar, Hussein S.; Amin, Ahmed M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: The acquired immunodeficiency syndrome (AIDS) is a disorders caused by cellular and humoral immune dysfunction from infection by the human immunodeficiency virus (HIV 1 and HIV 2).Patients and Methods: The study was carried out in Kirkuk governorate on 5090 secondary school students from different localities of the city, for the period from the beginning of October 2005 to the end of March 2006. A special questionnaire was applied for each student containing age, sex, class, parent’s education, mode of transmission & methods of prevention.Results: There was no significant difference between male and female regarding the etiology of AIDS.The knowledge of secondary school students was not related to parent's education.Conclusions: It is concluded that educational lectures increased the knowledge of students.